2009
DOI: 10.1099/mic.0.027508-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CRISPR in Streptococcus mutans suggests frequent occurrence of acquired immunity against infection by M102-like bacteriophages

Abstract: Clustered regularly interspaced short palindromic repeats (CRISPR) consist of highly conserved direct repeats interspersed with variable spacer sequences. They can protect bacteria against invasion by foreign DNA elements. The genome sequence of Streptococcus mutans strain UA159 contains two CRISPR loci, designated CRISPR1 and CRISPR2. The aims of this study were to analyse the organization of CRISPR in further S. mutans strains and to investigate the importance of CRISPR in acquired immunity to M102-like phag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 39 publications
4
71
0
Order By: Relevance
“…SMU.63 and SMU.1402, two genes known to be differentially regulated under CSP conditions (25), were first tested. SMU.1402 encodes a CRISPR-associated Csn2 protein belonging to the CRISPR-1 region of S. mutans (49). CRISPR arrays with CRISPRassociated proteins are involved in resistance to bacteriophage, and resistance specificity is determined by the insertion of CRISPR spacer-phage sequence similarity (50).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SMU.63 and SMU.1402, two genes known to be differentially regulated under CSP conditions (25), were first tested. SMU.1402 encodes a CRISPR-associated Csn2 protein belonging to the CRISPR-1 region of S. mutans (49). CRISPR arrays with CRISPRassociated proteins are involved in resistance to bacteriophage, and resistance specificity is determined by the insertion of CRISPR spacer-phage sequence similarity (50).…”
Section: Resultsmentioning
confidence: 99%
“…is insufficient to render sensitivity to infection by the phage M102 (49). Natural phage resistance mechanisms in S. mutans have not been previously described, mainly because phages and sensitive strains are actually quite rare in S. mutans (52).…”
Section: Figmentioning
confidence: 99%
“…Intriguingly, mutations in these active sites did not alter the affinity of the CRISPR/Cas complex for binding the protospacer (29). Importantly, protospacer-adjacent motifs (PAMs) that are short conserved nucleotide stretches next to the protospacers, such as NGG (32), NGGNG (22), NAAR (32), and NNAGAAW (33), are absolutely necessary for Cas9 binding and cleavage (29). Orthogonal Cas9 nucleases from different microorganisms require different PAM sequences (31,34).…”
Section: Type II Crispr/cas Systemmentioning
confidence: 99%
“…Despite this knowledge, the mechanisms responsible for resistance to M102 in S. mutans serotype c remain unknown. S. mutans strain UA159 harbors two distinct CRISPR-Cas systems: a type II-A CRISPR1-Cas system and a type I-C CRISPR2-Cas system (45)(46)(47)(48). The analysis of CRISPR cassettes in 29 S. mutans strains revealed that CRISPR spacers had high sequence similarity with M102, a virulent siphophage specific for S. mutans, suggesting that phage-derived spacers present in these strains likely resulted from M102-like phage attacks (45).…”
mentioning
confidence: 99%
“…Only five phages, designated M101, M102AD, M102, e10, and f1, have been shown to have lytic activity against S. mutans strains of serotypes c, e, and f, respectively (44,45). Except for S. mutans strain OMZ381, all S. mutans serotype c strains, including UA159, are known to be resistant to phage infection by M102; only strain OMZ381 showed sensitivity to phage infection, resulting in cell lysis (45). Despite this knowledge, the mechanisms responsible for resistance to M102 in S. mutans serotype c remain unknown.…”
mentioning
confidence: 99%